Cognitive assessment and rehabilitation tools for stroke and dementia: An online survey of Russian speaking clinicians. Issue 3 (4th May 2022) - Shendyapina, Maria; Su, I-Fan; Weekes, Brendan
Abstract: Our objective was to survey opinions on cognitive assessment and rehabilitation of Russian-speaking clinicians working with stroke and dementia patients. An online survey was circulated to professional communities soliciting feedback from clinicians about methods used for cognitive assessment and rehabilitation; expected cognitive impairments in dementia and stroke; variables affecting the cognitive abilities of patients; and topics presented during psycho-educational initiatives. Forty-eight physicians, 50 psychologists, and 12 speech-language pathologists completed the survey. 96% of participants reported estimating the cognitive abilities of patients while performing diagnostics and treatment in clinical settings. The most popular tools for cognitive assessment were Russian versions of the MoCA, MMSE, Luria Neuropsychological Battery, and Frontal Assessment Battery (FAB). 60% of participants reported the provision of cognitive rehabilitation, and 61% provided psychoeducation. All groups reported that the cognitive reserve and the idiopathic features of a brain lesion were the main factors influencing patients' cognitive profile. In the case of stroke patients, clinicians observed aphasia, as well as impairments in attention, memory, and reasoning. For patients with dementia, memory deficits were coincident with executive/frontal, praxis, and visuo-perceptual impairments. Psychotherapy-related psychoeducation was delivered by most of the clinicians. The captured patterns of clinical practice followed, in part, Russian national guidelines for cognitive rehabilitation and, in part, international protocols, wherein we found some professional group differences in implementation of practice. The profile in approaches to stroke and dementia assessment and rehabilitation reveal a new benchmark for future studies and for the development of policies for neuropsychological assessment and treatment in Russian language.